2007
DOI: 10.1063/1.2714772
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of ion-beam damage in lithium niobate

Abstract: The damage kinetics induced by irradiation with a diversity of swift ions ͑O at 5 MeV; F at 5.1 MeV; Si at 5, 7.5, and 41 MeV; and Cl at 11 and 46 MeV͒ has been investigated in the range of 10 12-10 15 at./ cm 2. It covers from the initial stage where single damage tracks are isolated and well separated, up to the stage where a full amorphous layer is produced. The damage is characterized by the areal fraction of disorder derived from the Rutherford backscattering/ channeling spectra. The data approximately fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…4 we plot the dependence of the Avrami parameters on stopping power S e ; the model's parameters obtained from the fit are also shown in Table 2. The dependence is in accordance with that obtained for other dielectric materials [28][29][30] and confirms a general trend: n > 1 for stopping powers below threshold and decreases down to an asymptotic value, n = l, for high enough stopping powers (S e > S th ) [30]. In other words, one should remark that the exponent n remains above 1 even for stopping powers somewhat higher than the threshold value.…”
Section: Data Analysis With An Avrami Kineticssupporting
confidence: 89%
See 2 more Smart Citations
“…4 we plot the dependence of the Avrami parameters on stopping power S e ; the model's parameters obtained from the fit are also shown in Table 2. The dependence is in accordance with that obtained for other dielectric materials [28][29][30] and confirms a general trend: n > 1 for stopping powers below threshold and decreases down to an asymptotic value, n = l, for high enough stopping powers (S e > S th ) [30]. In other words, one should remark that the exponent n remains above 1 even for stopping powers somewhat higher than the threshold value.…”
Section: Data Analysis With An Avrami Kineticssupporting
confidence: 89%
“…The disorder induced by the irradiation was measured by RBS channeling (RBS/C), with helium at 3.035 MeV [29,40]. Some typical RBS/C spectra, obtained from the samples irradiated with Cl +3 at 10 MeV, are illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amorphous fraction has been assessed by RBS/C channeling experiments. 7,33 One sees that in the cases of O and F, a certain prior or incubation fluence ⌽ is required to start full amorphization in comparison with Si ͑7.5 MeV/nm͒ where it starts at a much smaller fluence ͑in this case, ⌽ = ⌽ 0 is the overlapping fluence͒. The occurrence of an incubation fluence is also inferred from optical ͑dark-mode͒ data obtained for higher fluences, where a full homogeneous amorphous layer is induced.…”
Section: A Single Impact Experiments "Low Fluences…: Thresholdingmentioning
confidence: 86%
“…In this respect, it has been shown that a controlled damage can be generated by selecting the type of ion and its mass, energy and fluence, obtaining a micro-processing of crystals with a degree of accuracy, flexibility and efficiency well beyond the current state of the art. The optical waveguides produced with this method are both an end in itself (Caballero et al, 2005;Olivares et al, 2005bOlivares et al, , 2007cGarcía-Navarro et al, 2006;Manzano et al, 2010) and a mean that allows the precise study of several fundamental aspects of the generation and accumulation of electronic damage García-Navarro et al, 2007;Rivera et al, 2010a;García et al, 2011).…”
Section: Introductionmentioning
confidence: 99%